PEMAHAMAN KONSEP SISWA DALAM MENYELESAIKAN POLA BILANGAN PERKALIAN KELAS VIII SMPN 2 NANGA PINOH - Sugiono, Fani; Ferianti, Flesia Welly (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This study aims to describe students’ conceptual understanding in solving multiplication number pattern problems in Grade VIII of SMPN 2 Nanga Pinoh. A qualitative descriptive approach was employed, using written tests and in-depth interviews to obtain a comprehensive depiction of students’ thinking processes. Data validity was ensured through technique triangulation, allowing the findings to be more accurate and trustworthy. The results show that students’ conceptual understanding is categorized as very good, with an average score of 90,96 and 83.33% of students meeting the mastery criterion. High-achieving students demonstrated the ability to recognize numerical regularities, determine relationships between terms, and correctly apply the formula . However, students in the medium and low categories still experienced difficulties in identifying ratios and generalizing patterns into symbolic forms. Differences in learning outcomes were influenced by students’ logical thinking abilities, the teacher’s instructional strategies, and students’ reflective skills in evaluating their solutions. Discovery learning and scaffolding approaches were found to effectively support more meaningful and in-depth understanding of multiplication number patterns. ABSTRAK Penelitian ini bertujuan mendeskripsikan pemahaman konsep siswa dalam menyelesaikan soal pola bilangan perkalian di kelas VIII SMPN 2 Nanga Pinoh. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik pengumpulan data berupa tes deskriptif dan wawancara mendalam untuk menggali proses berpikir siswa secara lebih komprehensif. Keabsahan data dijamin melalui triangulasi teknik sehingga temuan yang diperoleh lebih akurat dan dapat dipercaya. Hasil penelitian menunjukkan bahwa pemahaman konsep siswa tergolong sangat baik, dengan rata-rata nilai 90,96 dan 83,33% siswa mencapai KKM. Siswa berkemampuan tinggi mampu mengenali keteraturan pola, menentukan hubungan antar suku, serta menerapkan rumussecara tepat. Namun, siswa kategori sedang dan rendah masih mengalami kesulitan dalam menentukan rasio serta menggeneralisasikan pola ke bentuk simbolik. Perbedaan hasil belajar dipengaruhi oleh kemampuan berpikir logis, strategi pembelajaran guru, dan kemampuan reflektif siswa dalam menyebarkan langkah penyelesaiannya. Pendekatan pembelajaran penemuan (discovery learning) dan bimbingan bertahap (scaffolding) terbukti membantu siswa memahami pola bilangan secara lebih bermakna dan mendalam.